The COVID-19 Pandemic and Its Influence on Slovak Media Professionals - Tomková, Šimona; Gálik, Slavomír; Kapec, Miroslav (Communication Today, 2024)
The research focuses on the status of media coverage of the COVID-19 pandemic by media professionals in Slovakia. Out of a representative research sample calculated to be 242 reporters out of a total of 2,130 reporters in Slovakia, only 50 reporters responded to the questionnaire, which is also a limitation of this research. From the responses, the authors generated the current status of media coverage of the COVID-19 pandemic. Positive results of the questionnaire survey include that most of the media reporters tried to rely on the opinions of experts such as epidemiologists, virologists, etc. Also, 64% of the respondents did not feel any restriction of freedom in their work. The high percentage of self-study by reporters should also be added to the positive phenomena. On the negative side, as many as 56% of the respondents stated that it was not important for them to influence public opinion, and a smaller percentage also mentioned various influences that interfered with the impartiality and objectivity of reporting. Also, a high percentage of respondents were critical of the government’s management of the pandemic. Based on these findings, it can be concluded that the state of media coverage in Slovakia during the COVID-19 pandemic was not entirely optimal. Further research should complement and refine the picture of the Slovak media at the time of the COVID-19 pandemic.